Duration of fever and PA/I38X-substituted virus emergence in patients treated with baloxavir in the 2018–2019 influenza season. Issue 4 (April 2020) - Ikematsu, Hideyuki; Kawai, Naoki; Tani, Naoki; Chong, Yong; Iwaki, Norio; Bando, Takuma; Tanaka, Osame; Matsuura, Shinro; Maeda, Tetsunari; Doniwa, Kenichi
Abstract: Duration of fever and virus persistence after baloxavir administration were investigated in 81 outpatients, 16 with A(H1N1)pdm09 and 65 with A(H3N2) in the Japanese 2018–2019 influenza season. Only eight cases of A(H3N2) viruses were detected post-dose. PA/I38T-substituted viruses were detected in four (6.2%) of 65 A(H3N2) patients, at days 3 and 4, constituting 50% (4/8) of A(H3N2) detected post-dose. The median duration of fever was 26.0 h for A(H1N1)pdm09 and 20.3 h for A(H3N2). The median duration of fever for patients with PA/I38T-substituted viruses was 22.0 h, without significant difference to that of the patients in whom the mutated virus was not detected. Emergence of PA/I38T-substituted viruses after treatment with baloxavir was confirmed, but no significant prolongation of fever was observed in the four patients with PA/I38T-substituted virus emergence.